STRATEGI TRANSFORMASI DIGITAL LAYANAN INFORMASI PADA DINAS PERPUSTAKAAN DAN KEARSIPAN DAERAH KABUPATEN SAMBAS - ALI SANDER (Jurnal Komunikasi, 2026)
This article aims to analyse the digital transformation strategy for information services at the Sambas Regency Regional Library and Archives Office through a literature review approach. The research findings indicate that, empirically, the management of archives and information services at regional library institutions still faces challenges in terms of infrastructure, human resource competencies, the strengthening of digital systems, and service governance that is not yet fully integrated. On the other hand, digital transformation is capable of improving service efficiency, expanding access to information, supporting the preservation of collections, and strengthening the relevance of regional libraries in an era of fast-paced information needs. The most important strategies include analysing service needs, strengthening digital governance, developing information technology infrastructure, digitising priority collections and archives, enhancing the competencies of librarians and archivists, developing user-centred service platforms, and conducting continuous evaluation of service quality. With a well-planned and phased strategy, the Sambas Regency Regional Library and Archives Service has the opportunity to build information services that are more effective, adaptive, inclusive and responsive to the needs of the local community in the digital age.